Intimal Thickness of the Right Renal Artery: A Postmortem Study (Bangladesh Journal of Anatomy, 2010)
Context: Atherosclerosis is the most frequent intimal disease of large and medium sized arteries. It is characterized by the intimal thickening and lipid deposition. Atherosclerosis can affect the kidneys directly by renal stenosis or as a frequent site of atherosclerotic disease. The seemingly increased incidence of atherosclerotic disorders in the country, their fatal consequences and the paucity of relevant data of the present study was carried out to find out such information which help workers at all levels playing their roles in planning and execution of the prevention and management aspects of atherosclerotic disorders. Study design: The study was observational, cross sectional & analytical in nature. Place and period of study: Department of Anatomy, Sir Salimullah Medical College, Dhaka, during the study period of 2005 to 2006. Materials and Methods: Six good Mallory-Azan stained histological slides, section from proximal 2cm of right renal arteries of three age groups (lower 8-29 years, middle 30-40 years, higher 42-92 years) were prepared for this study. After standardizing the ocular micrometer with the stage micrometer for the particular objective and eyepiece, each study slide was placed in the place of stage micrometer and intimal thickness was measured in ocular micrometer division. Result: The present study revealed that mean intimal thickness increased along with increasing age. Unpaired student ‘t' test for statistical analysis revealed significant differences (p